Kinesis : the ancient depiction of gesture, motion, and emotion : essays for Donald Lateiner - Lateiner, Donald; Clark, Christina A.; Foster, Edith (Edith Marie); Hallett, Judith P., 1944- (Ann Arbor : University of Michigan Press, 2015)
Donald Lateiner, in his groundbreaking work The Sardonic Smile, presented the first thorough study of nonverbal behavior in Homeric epics, drawing a significant distinction between ancient and modern gesture and demonstrating the intrinsic relevance of this "silent language" to psychological, social, and anthropological studies of the ancient world. Using Lateiner's work as a touchstone, the scholars inKinesisanalyze the depiction of emotions, gestures, and other nonverbal cues in ancient Greek and Roman texts and consider the precise language used to depict them. Individual contributors examine genres ranging from historiography and epic to tragedy, philosophy, and vase decoration. They explore evidence as disparate as Pliny's depiction of animal emotions, Plato's presentation of Aristophanes' hiccups, and Thucydides' use of verb tenses. Sophocles' deployment of silence is considered, as are Lucan's depiction of death and the speaking objects of the medieval Alexander Romance. This collection will be valuable to scholars studying Greek and Roman society and literature, as well as to those who study the imitation of ancient literature in later societies. Jargon is avoided and all passages in ancient languages are translated, making this volume accessible to advanced undergraduates.--Provided by publisher
Kinesis in the perface to Thucydides / Jeffrey Rusten -- Natural upheavals in Thucydides (and Herodotus) / Rosaria Vignolo Munson -- Action and consequences : the hisotrical present tense in the opening narratice of book 8 of Thucydides / Edith Foster -- Herodotus and Thucydides on not learning from mistakes / Hans-Peter Stahl -- Speaking silences in Herodutus and Sophocles / Carolyn Dewald and Rachel Kitzinger -- Two tales of Spartan envoys / Deborah Boedeker -- Gorgias in the real world : Hermocrates on interstate stasis and the defense of Sicily / Daniel P. Tompkins -- Manly matters : gender, emotion, and the writing of history / John Marincola -- Masculinity, noverbal behavior, and Pompey's death in Lucan's bellum ciuile / Christina A. Clark -- Nonverbal behavior in Seneca's phaedra / Carolyn Hahnemann -- Elephant tears : animal emotion in Pliny and Aelian / Ellen Finkelpearl -- Lucian's coutesans : vulnerable women in a difficult occupation / Hanna M. Roisman -- Omnia movet amor : love and resistance, art and movement, in Ovid's Daphne and Apollo episode (Metamorphoses 1.452-567) / Judith P. Hallett -- Verbal behavior in the iliad / Eliot Wirshbo -- Shipwreck narratives in Homer's odyssey and Coetzee's foe / James V. Morrison -- Phrontiserion 2.0 : Arisophanes' clouds and Plato's critique of pedagogies in the symposium / Bruce Heiden -- Hephaestus' winged shoes and birth of Athena / Daniel P. Levine -- From papyrus to peppercorns : the tradition of significant objects in the Alexander romance / Brad L. Cook.
Includes bibliographical references (pages 295-309) and index.
Description based on print version record; resource not viewed.
English.
JSTOR
Keywords: Greek literature -- History and criticism; Latin literature -- History and criticism; Motion in literature; Gesture in literature; Littérature grecque -- Histoire et critique; Littérature latine -- Histoire et critique; Mouvement dans la littérature.; LITERARY CRITICISM -- Ancient & Classical; LITERARY COLLECTIONS -- Ancient & Classical; Gesture in literature; Greek literature; Latin literature; Motion in literature; Criticism, interpretation, etc